Critical success factors for project management in the education sector in South Africa - Nirghen, Randir Rajkumar (My University, 2012)
The South African education system suffers from the legacy of decades of social and economic discrimination against black South Africans. This situation continues despite there being numerous projects to improve the situation. The education sector is a complex environment. Project management methodologies and processes are used to deliver projects successfully in complex environments. There are several critical success factors of project management that ensure successful project implementation. The aim of this study was to assess the use of available project management methodologies and processes for project management in the education sector in South Africa and identify the critical success factors. The qualitative research methodology was used for this study. Data was collected through semi-structured interviews with organisations implementing projects in the education sector. The content analysis method within the interpretive analysis method of the transcribed interview data was employed. The results indicate that the organisations are using project management methodologies or processes. The organisations have chosen internal systems or tailoring the standard project methodologies to suit the organisations needs. Most of the organisations are using these processes and methodologies to a high degree with the remaining using it but to a lesser degree. The study identified the critical success factors of projects in the education sector. These factors are sector specific factors, internally derived processes and key competencies of the project manager. The sector specific factors are budget, planning, the ability to deal with human behaviour, time, quality, monitoring and evaluation, change management, governance, resource planning, stakeholder requirements, satisfaction and acceptance/usage, design must be thoroughly researched and substantiated, lessons learnt, ability to show the benefit of the projects, partnering and taking on projects based on the government strategy. The Internally derived processes are scope, schedule, cost and resource management as well as regular meetings and reporting. The key competencies of a project manager are conventional project management skills, communication skills, people management, the ability to mobilise people and collaboration These organisations in the education sector should combine the methodologies with the critical success factors when implementing their projects. They should investigate whether adding the evolve stage, working with government and partnering could assist in tackling the problems in education in South Africa.
MBA thesis - WBS
Keywords: Critical succes factors in Education; Education sector